An Improved Proposed Single Phase Transformerless Inverter with Leakage Current Elimination and Reactive Power Capability for PV Systems Application - Fahad Almasoudi; Mohammad Matin (Journal of Low Power Electronics and Applications, 2018)
Single-phase transformerless inverters are broadly studied in literature for residential-scale PV applications due to their great advantages in reducing system weight, cost and elevating system efficiency. The design of transformerless inverters is based on the galvanic isolation method to eliminate the generation of leakage current. Unfortunately, the use of the galvanic isolation method alone cannot achieve constant common mode voltage (CMV). Therefore, a complete elimination of leakage current cannot be achieved. In addition, modulation techniques of single-phase transformerless inverters are designed for the application of the unity power factor. Indeed, next-generation PV systems are required to support reactive power to enable connectivity to the utility grid. In this paper, a proposed single-phase transformerless inverter is modified with the clamping method to achieve constant CMV during all inverter operating modes. Furthermore, the modulation technique is modified by creating a new current path in the negative power region. As a result, a bidirectional current path is created in the negative power region to achieve reactive power generation. The simulation results show that the CMV is completely clamped at half the DC link voltage and the leakage current is almost completely eliminated. Furthermore, a reactive power generation is achieved with the modified modulation techniques. Additionally, the total harmonic distortion (THD) of the grid current with the conventional and a modified modulation technique is analyzed. The efficiency of the system is enhanced by using wide-bandgap (WBG) switching devices such as SiC MOSFET. It is observed that the efficiency of the system decreased with reactive power generation due to the bidirectional current path, which leads to increasing conduction losses.